O uso de verbos cognitivos em construções parentéticas epistêmicas: uma abordagem do ponto de vista da gramaticalização - Barbosa, Letícia de Almeida (2019)
This study takes cognitive verbs as the object of research, which express more and less specific mental processes, such as reasoning, knowledge, beliefs, judgments and positioning of the speaker with respect to a content. They are verbs as crer, achar, pensar, acreditar, imaginar, supor, deduzir and others, which are often clause-embedding verbs, in clauses in internal argument position. Despite its typical functioning, as a predicate, they can act as independent textual units of the sentence’s basic structure, having as domain the whole enunciation or part of it. Because they are extraclausal and suspend the developing topic, to give rise to a speaker's attitude, they can be called parenthetical. Considering that, many cognitive verbs express, in addition to activities of reasoning and knowledge, the speaker’s positioning towards the proposition, the senses of a small set of cognitive verbs are analyzed in this work, in order to capture nuances that provide an exchange between the field of cognitive and the field of epistemic modality, which strengthens the expression of attitude and belief in some contexts. In considering that these verbs tend to approach the epistemic modality field, grammaticalization here is understood in the wider sense, as stated by Hopper; Traugott (1993) and Himmelmann (2004), authors who do not point the change of category as a preponderant change, favouring changes of semantic-pragmatic behavior and expansion. By analyzing the semantic senses of the verbs crer, acreditar, supor, pensar, achar, imaginar, deduzir and calcular, it was possible to observe the performance of syntactic mechanisms but, above all, semantic mechanisms in the trajectory of abstratization. From this perspective, the identification of grammaticalization mechanisms that provide more abstract uses, under the assumption that, when parentheticalized, there is more visibility of its modalizator character, due to the fact that the speaker launches a statement and then a proviso, relativising the veracity of the content stated and highlighting how it relates to the proposition. In the analysis, studies such as Traugott; Dasher (2001); Thompsom; Mulac (1991); Gonçalves (2003; 2004; 2007); Casseb-Galvão (2004) and Fortilli (2013) have been used as a basis. For analysis and interpretation of the results, data from the 19th, 20th and 21st centuries were collected from the Portuguese corpus, which is available online. Thus, in addition to the abstratization process, it was possible to observe the increase in the frequency of occurrence with parentheticalized cognitive verbs in Portuguese.